Croatian Ethnogesis and the Nomadic Element - Heršak, Emil; Nikšić, Boris (2007)
In the paper, the authors will attempt to present certain parameters dealing with the nomadic element, or possible indications of it, in Croatian/Croat ethnogenesis. First, a comment will be given of the ethnogenetic concept itself, and a working definition of ethnogenesis will be suggested. Second, the major com¬ ; ; ponents that are considered to have had a role in Croatian ethnogenesis will be listed. This discussion will be followed by an identification of those elements that could somehow be considered nomadic, or else representative of influences from the Eurasian steppe region. Mention will be made of historical sources that confirm or imply the presence of Eurasian nomad groups in the Croatian area, and the relative frequency of archaeological material will be noted. The authors will comment on the views of previous and present Croatian and foreign authors on Croatian ethnogenesis, especially in regard to the “ Eurasian connection” . In this part of the discussion, the Iranian theory of Croat origins will be presented in more detail. Finally, the authors will briefly comment on recent genetic (DNA) analyses of the contemporary Croatian population.
Projekt MZOS
ENG